A COMPREHENSIVE REVIEW ON NIOSOMES - Preeti Budhlakoti; Kapil Kumar; Deepak Teotia (Journal of Biomedical and Pharmaceutical Research, 2020)
Niosomes are a bilayered non-toxic, non-immunogenic nanoparticular delivery system; it is being used for drug delivery. Owing to its cost-effectiveness and easy manufacturing processing, niosomes are gaining popularity as a coveted drug carrier. Main constituents of a niosomes are cholesterol and a non-ionic surfactant, although several additives like charged molecule (Solulan C24) can be added to modify the surface charge of the particle and enhance its stability. There are various methods of manufacturing niosomes like hand shaking method, micro fluidization, sonication, bubble method to name a few. The fact that niosomes are amphiphillic molecules make them a versatile drug carrier as they can entrap both hydrophilic and lipophillic drugs. Applications of niosomes in the pharmaceutical industry therapeutic use, some of the most important ones being as cosmoceuticals, etc. In this review an effort has been made to document the key concepts relating to niosomes and the advances that have been made in terms of research in the field of niosomal drug delivery. Keywords: niosomes, nanoparticles, cholesterol, carrier, non-ionic, vesicles.